Kondisi Lingkungan Kerja Dan Tekanan Kerja Terhadap Minat Keluar Dari Pekerjaan Oleh Karyawan - Riyang Pambudi; Mega Nenda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to investigate the influence of work environment conditions and work pressure on employees' interest in leaving work. Through data collection using surveys and statistical analysis, this research evaluates the relationship between work environment conditions, work pressure, and interest in leaving work. It is hoped that the results of this research will provide useful insights for human resource management in improving the quality of the work environment and reducing employee turnover rates.